THE EXISTENCE OF CAPITAL STRUCTURE TARGET AND SPEED OF ADJUSTMENT: EVIDENCE FROM INDONESIAâS CONSUMER GOODS COMPANIES - Rita Sahara, Yayang
Capital structure decisions have the critical role towards the objective of maximizing firm value. However, capital structure might be different between firms in developing and firms in developed countries. Indonesia is developing country which has high inflation rate and high interest rate. According to Bhate (2008), in an inflationary country, firms tend to avoid using long term debt. This work is aims to analyze the capital structure characteristic of Indonesian public firms depends by its specific microeconomic factors. Thus, the objectives of this research are to identify firm-specific factors that determining the capital structure decision of Indonesian public firms, then investigate the existence of capital structure target with firm-specific factors that determining its target capital structure, and after that identify how fast the its adjustment speed. Secondary data of 10 years financial statements of 10 public firms under consumer goods industry starts from 2005 to 2014 were collected to be analyzed using unbalanced panel data regression. This analysis leads to test two complementary successive econometric models, the first is a static and the second is dynamic model. By employs Generalized Least Squared effect, this study provide the new empirical evidences from Indonesian public firm behavior. In static model, asset tangibility and firm liquidity show the statistically significant relationship with capital structure while in dynamic model, asset tangibility, growth opportunity, and firm liquidity appears significant effect to the target capital structure. The most remarkable result from this research is that there is the evidence whether over the time, Indonesia’s consumer goods companies tend to move towards target capital structure by the adjustment speed of 42.16% per year or they would be able to fully adjust their capital structure in 8 years and 5 months. This results are consistent with the trade-off theory of capital structure. Finally, this research attempts to contribute deeper understanding about financing decision occupied by Public firms in Indonesia.